2012
DOI: 10.1016/j.agwat.2011.10.021
|View full text |Cite
|
Sign up to set email alerts
|

APEX simulation of best irrigation and N management strategies for off-site N pollution control in three Mediterranean irrigated watersheds

Abstract: Simulated annual values were in general more accurate than simulated monthly values. 13 APEX predicted that improving irrigation management (change of irrigation system 14 and/or scheduling) will decrease N loads in IRF over current values by 45% (Akarsu), 15 40% (La Violada), and 8% (Sidi Rached). However, improved N fertilization only will 16 reduce N loads in IRF by 17% (Akarsu) or below 5% (La Violada and Sidi Rached). 17Improving irrigation management will increase IRF NO 3 -N concentrations by 19% in La … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Recently, best management techniques such as drip irrigation [26] and rain water harvesting techniques [27] have been tried to put into practice in order to save both irrigation water and fertilizers. In the Mediterranean climate, irrigation is inevitable for maximizing the crop yield [28]. To increase crop yield and quality and at the same time to decrease the leaching below the rooting zone, managing nutrient concentrations in irrigation water is necessary, according to crop requirements [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, best management techniques such as drip irrigation [26] and rain water harvesting techniques [27] have been tried to put into practice in order to save both irrigation water and fertilizers. In the Mediterranean climate, irrigation is inevitable for maximizing the crop yield [28]. To increase crop yield and quality and at the same time to decrease the leaching below the rooting zone, managing nutrient concentrations in irrigation water is necessary, according to crop requirements [29].…”
Section: Introductionmentioning
confidence: 99%
“…The current study, using the APEX model, simulates a net irrigation supply of 638 mm and a maize yield of 11.1 t ha −1 , while in an earlier study, employing the AquaCrop model (Steduto et al, 2011), we simulate an irrigation supply of 630 mm and a maize yield of 11.9 t ha −1 (Chukalla et al, 2015). APEX is reported to adequately simulate evapotranspiration for different management practices with the Penman-Monteith equation for semi-arid conditions in the Mediterranean, including Spain (Cavero et al, 2012). The study by Milly and Dunne (2016), however, reported that Penman-Monteith overestimates evapotranspiration for non-water stress conditions, which suggests that ground-truthing with field experiments is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Located in Mitidja's western plain, the study has focused on Sidi Rached aquifer where high concentrations of nitrates have been recorded mainly caused by intensive and unsustainable agricultural practice [1,2]. Indeed, a number of studies has established that nitrate concentrations in groundwater were ranging from 20 mg/L to more than 200 mg/L and that the source of this pollution emanates from the leeching of chemical fertilizers (ammonium nitrate, ammonium phosphate and potassium sulphate) [3][4][5]. Nitrogen, in particular in the form of nitrates, being very soluble, generally reaches groundwater dissolved in percolating water and it is the most common aquifer contaminant [6].…”
Section: Introductionmentioning
confidence: 99%
“…The APEX (Agricultural Policy Environmental EXtender model) was used to assess the best management practices for reducing off-site N loads in the IRF (Irrigation Return Flow) of three Mediterranean irrigated watersheds (Akarsu in Turkey, La Violada in Spain and Sidi Rached in Algeria) [4]. Overall, APEX simulated that the improvement of irrigation performance was the best management strategy to decrease off-site N pollution.…”
mentioning
confidence: 99%